Integrating Diagnostics, Modularity, and Cultural Contexts: A DMC Framework for Adaptive Learning in Indonesian Secondary Schools - Latifah Latifah; Dirgantara Wicaksono; Asep Saefullah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Adaptive learning platforms (ALPs) in Indonesia's secondary education are growing, yet often emphasize technical performance while neglecting learner diagnostics and socio-cultural relevance. This study addresses the need for a more holistic framework that integrates diagnostic assessment, modular instruction, and cultural contextualization. Using a case-informed literature review approach, the study examined adaptive learning practices in eight diverse institutions—four junior high schools (SMP) and four Islamic junior high schools (MTs)—selected for their innovation and regional representation. Data sources included academic literature, institutional documentation, and digital platform analysis. Findings revealed two key trends: SMPs tend to excel in implementing AI-driven diagnostics and modular pathways, while MTs emphasize cultural and religious integration in content design. However, neither school type fully integrates diagnostics with contextualized learning. Based on these insights, the study proposes the DMC (Diagnostic–Modular–Culture) framework, comprising: (1) individualized diagnostics via pre-assessment tools, (2) differentiated modular learning tracks (remedial, standard, enrichment), and (3) integration of socio-cultural content into instructional design. The DMC model offers a scalable, inclusive framework for adaptive learning tailored to Indonesia’s educational diversity. Its implementation supports personalized instruction while reinforcing learner identity and cultural engagement, aligning with the principles of Kurikulum Merdeka.